Do dividends still matter? The role of investment opportunities on the ability of dividends to predict future earnings - Sila Ninin Wisnantiasri (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study investigates the role of firm characteristics explained by the investment opportunity (IO) on the ability of dividends to predict future earnings.Design/Methodology/Approach: This study performed an empirical study on firms listed in the consumer goods sub-sector on the Indonesian Stock Exchange, divided into companies with strong and weak IO categories to clearly see the role of IO by comparing the variable dividend coefficients of the two sample categories. Through purposive sampling, the researcher determined the research sample, totaling 42 firm samples for the weak IO category and 48 firm samples for the strong IO category. Then, the multiple regression analysis utilizing IBM SPSS Statistic Version 23 was employed to analyze the relationship between variables.Research findings: Surprisingly, companies with weak IO showed a more remarkable ability to predict future earnings than companies with strong IO because the dividend coefficient of companies with weak IO was higher than that of strong IO, denoting that the number could explain the strength of ability.Theoretical contribution/Originality: The result provides alternative explanations to the previous inconsistent results from the dividend's ability to predict future earnings. The result also supports the argument that the companies with weak IO may use dividends to convey information signals and compensate the investor for unsatisfied performance, which is called counter-signal when strong IO refrain from doing so and rely on additional information.Practitioner/Policy implication: Investors should notice companies' characteristics, such as investment opportunities, while considering dividends as a signal for future performance to make an investment decision. Research limitation/Implication: The research did not fully capture all companies in Indonesian Stock Exchange, but specifically for the companies’ sub-sector that aggressively paid the dividend. Thus, future research is hoped to provide empirical studies for other sector companies listed on Indonesia Stock Exchange to enrich alternative explanations.